REAL TIME MOTION DETECTION ON DYNAMIC SCENES STUDY AND IMPLEMENTATION WITH RECONFIGURABLE TECHNOLOGY - MOSTEFAI, M.; ZITOUNI, B.; ROUSSEL, M. (Courrier du Savoir, 2014)
ABSTRACT Moving objects extraction from dynamic scenes is a well used approach in applications that requires high compression rates such as surveillance. Unfortunately, the different operators developed to undertake this operation and that use often classical edge detection techniques in their processing remains very sensitive to noise. Different approaches where used to resolve this problem. Among these, fuzzy approach is recently used to develop robust operators less sensitive to noise. The aim of this work is to present a fuzzy edges detector used by a moving objects extraction operator, and its implementation within an FPGA circuit of XILINX for a real time images processing. Key words : Image processing - Motion detection - Fuzzy logic - Real time - Reconfigurable technology RESUME L'extraction d'objets mobiles à partir de scènes dynamiques est une technique très utilisée dans les applications qui exigent des taux de compression élevés telle la surveillance. Malheureusement, les différents opérateurs développés pour effectuer cette opération et qui utilisent souvent des techniques d’extraction classiques sont très sensibles au bruit. Différentes approches ont été proposées pour résoudre ce problème. Parmi celles ci, l'approche floue. Cette dernière est récemment employée pour développer des opérateurs robustes moins sensibles au bruit. Le but de ce travail est de présenter un détecteur de contours d’objets mobiles basé sur l’approche floue ainsi que son implémentation dans un circuit de type FPGA de XILINX pour un traitement d’images en temps réel.